2020
DOI: 10.3390/antiox9090899
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 Phenotype and Protein N-Homocysteinylation in Patients with Rheumatoid Arthritis: Implications for Cardiovascular Disease

Abstract: Paraoxonase 1 (PON1) is the high density lipoprotein-associated esterase which inhibits the development of atherosclerosis by metabolizing lipid peroxidation products as well as hydrolyzing proatherogenic metabolite of homocysteine (Hcy), Hcy thiolactone, which otherwise reacts with lysine groups of proteins, thus forming N-Hcy-protein in a process referred to as protein N-homocysteinylation. Rheumatoid arthritis (RA) is the chronic inflammatory autoimmune disease associated with increased risk of cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…Furthermore, PON1 levels negatively correlated with DAS28 scores. Parada‐Turska et al showed that both activity and level of PON1 were decreased in RA patients and these decrease associated with disease activity 28 . Besides, decreased PON1 levels have also been shown to be associated with increased CVD 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PON1 levels negatively correlated with DAS28 scores. Parada‐Turska et al showed that both activity and level of PON1 were decreased in RA patients and these decrease associated with disease activity 28 . Besides, decreased PON1 levels have also been shown to be associated with increased CVD 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Parada-Turska et al showed that both activity and level of PON1 were decreased in RA patients and these decrease associated with disease activity. 28 Besides, decreased PON1 levels have also been shown to be associated with increased CVD. 29 Shevchuk et al demonstrated that the PON1 activity in RA patients is associated with several CVD diseases such as atherosclerotic vascular damage and myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, it has been suggested that various factors might be implicated in the pathogenic mechanisms of such a condition, including underlying grounds of diabetes mellitus and rheumatoid arthritis [46]. An important consideration when evaluating the onset of CVDs is the close investigation of other entities that may run ahead and parallel with the CVDs and are effectively served by inflammation, tissue damage, and macrovascular circulation-related issues [47,48]. The results include the development of atheromatosis or atherosclerosis, carotid plaque, and luminal narrowing of arteries [49], with most severe endpoints being stroke, myocardial infraction, and mortality.…”
Section: Findings In Contextmentioning
confidence: 99%
“…Author details 1 The First School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou 310053, China. 2 School of Basic Medical Sciences, Zhejiang Chinese Medical University, Hangzhou 310053, China. 3 The Second A liated Hospital of Zhejiang Chinese Medical University, Hangzhou 310005, China.…”
Section: Fundingmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a common and chronic autoimmune disease, characterized by synovial in ammation, pannus formation and joint destruction, eventually leading to joint dysfunction and decreased quality of life [1,2]. Previous epidemiological surveys demonstrated that the global incidence of RA is 0.5-1% [1].…”
Section: Introductionmentioning
confidence: 99%